Resolution of (1RS, 3RS)-2-N,N´ -Dimethyl-aminomethyl-1,3 dithiolane-1,3-dioxide Using Optically Active Acids - Gultekin, Zeynep (Asian Journal of Chemistry, 2010)
Racemic (1RS,3RS)-2-N,N´-dimethylaminomethyl-1,3-dithiolane-1,3-dioxide is resolved by formation of salts with chira1 acids [such as (1S)-(+)-10-camphorsulphonic acid, (-)-dibenzoyl-L-tartaric acid, (R)-(-)mandelic acid]. The best solvent for recrystallization of the diastereomeric mixture is found to be propionitrile and gave 68% ee.